Physico-chemical Parameters of Parthenium in Nagercoil, Tamil Nadu, India - Starlin Kamala, C.; Umayoru Bhagan, V. (Asian Journal of Chemistry, 2016)
Parthenium possesses harmful and useful properties. The samples of leaves and flowers were collected during September and February from the different locations of Nagercoil, Tamil Nadu. Physico-chemical parameters, viz., percentage of moisure, ash content, solubility in cold and hot water, NaOH and HCl were estimated and reported.